Energy policy and energy market performance: The Argentinean case - Recalde, Marina Yesica (2011)
In the early 1990s Argentina liberalized and privatized the energy system, trending to a total market oriented system and abandoning the use of energy policy. Since 2004, as a result of a boom in energy demand and constrains in energy supply, Argentina has gone through an energy problem mainly related to natural gas and electricity, which derived in energy shutdowns. In this frame, this study explores the role of energy policy and institutions in Argentina, with the aim of discussing whether it has been properly used to contrast the observed lack of coordination between fossil energy reserves management and the demand of fuels in power generation. The results of the analysis enhance the relevance of regulatory and control authorities, as well as the active use of long run energy policy for the energy system performance in order to avoid coordination failures between subsectors of the system. The relevance of energy consumption for the development process, and the particular characteristics of energy systems require a wide planning perspective.